THE QUALITY OF WORK LIFE AND ITS IMPACT ON IMPROVING THE PERFORMANCE OF HUMAN RESOURCES (THE GENERAL ADMINISTRATION OF HUMAN RESOURCES AT IMAM UNIVERSITY) - Khalid Albusair, (PEOPLE: International Journal of Social Sciences, 2025)
The study aimed to identify the impact of quality of work life in improving the performance of human resources in the General Administration of Human Resources at Imam Muhammad bin Saud Islamic University in the year 2024, from the point of view of the human resources employees of the university, which numbered (214) individuals, of whom (133) responded, the descriptive survey method was chosen, and the questionnaire was chosen as a tool for the study, and the tool consisted of five sections: The variables of the study, and the impact of quality of work life in improving the performance of human resources for the dimensions of: Fair and adequate compensation, safe and healthy working conditions, career growth opportunities, and clarity of rules and regulations in the organization of work:- The study found that the respondents agreed to a "great" extent on the impact of quality of work life in improving the performance of human resources in fair and appropriate compensation, and agreed to a "very great" extent on the axis of safe and healthy working conditions, career growth opportunities, and clarity of rules in the organization of work. The study showed that there are no statistically significant differences in the responses of the study members in all axes of the questionnaire due to the study variables, and based on the findings of the study, the researcher wrote a number of recommendations.